2023
DOI: 10.1186/s12879-023-08384-9
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of hemoglobin and 28-day mortality in septic patients: secondary data mining using the MIMIC-IV database

Abstract: Background Previous studies found minimal evidence and raised controversy about the link between hemoglobin and 28-day mortality in sepsis patients. As a result, the purpose of this study was to examine the association between hemoglobin and 28-day death in sepsis patients by analyzing the Medical Intensive Care IV (MIMIC-IV) database from 2008 to 2019 at an advanced medical center in Boston, Massachusetts. Methods We extracted 34,916 sepsis patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…13 Therefore, regardless of how high hemoglobin may be after being reduced relative to prior values while an unabated insult precipitates increasing severity in the patient in whom this most durable recovery mechanism has failed or how high hematocrit may have been made by this mechanism before its failure, death becomes the fate of the patient without therapeutic modification that permits recovery. Clinical reality accommodates this consequence in those empirical findings that show, with U-shaped 1,23,24 or J-shaped 24 curves, that in addition to the established association between early lower hemoglobin and higher risk of death, higher hemoglobin is also associated with a significant risk of COVID-19, 23 sepsis, 1 cardiovascular and all-cause mortality 24 as well as those revealing similar nonlinear associations between hematocrit and mortality. [25][26][27] The deaths which have been hitherto attributed to lower hemoglobin are prevented despite persistent failure of the recovery mechanism that increases cellular hemoglobin…”
Section: Long Covid and Other "Post-acute" Conditions Are Due To Abat...mentioning
confidence: 84%
See 1 more Smart Citation
“…13 Therefore, regardless of how high hemoglobin may be after being reduced relative to prior values while an unabated insult precipitates increasing severity in the patient in whom this most durable recovery mechanism has failed or how high hematocrit may have been made by this mechanism before its failure, death becomes the fate of the patient without therapeutic modification that permits recovery. Clinical reality accommodates this consequence in those empirical findings that show, with U-shaped 1,23,24 or J-shaped 24 curves, that in addition to the established association between early lower hemoglobin and higher risk of death, higher hemoglobin is also associated with a significant risk of COVID-19, 23 sepsis, 1 cardiovascular and all-cause mortality 24 as well as those revealing similar nonlinear associations between hematocrit and mortality. [25][26][27] The deaths which have been hitherto attributed to lower hemoglobin are prevented despite persistent failure of the recovery mechanism that increases cellular hemoglobin…”
Section: Long Covid and Other "Post-acute" Conditions Are Due To Abat...mentioning
confidence: 84%
“…For as long as the real link between the variables in the model and the clinical outcome has remained unclarified because observational studies can only observe the relationship between the two without determining causality, the life-threatening organ dysfunctions that are attributed to poor host response to an infectious illness in sepsis patients have continued to rank among the leading causes of inpatient death globally. 1 But empirical findings on the basis of which the persistent organ failure which has been described as the more common pattern before death in patients with severe sepsis 2 has also been concluded to be the cause of cancer deaths that occur despite the effort to reduce tumor burden at the oncology ward 3 suggest the following hypothesis towards the nature of this link. The same mechanistic process underlies death due to pathological phenomena in all patients regardless of the etiological factors that are involved in severity precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in patients with transfusion-dependent thalassemia, those with high serum ferritin levels are more likely to develop A. baumannii sepsis [29]. On the other hand, hypohemoglobinemia leads to direct mechanisms of injury related to nitric oxide scavenging, exacerbating acid-base metabolic imbalances and worsening cardiac, pulmonary, and other multiorgan failures [30][31]. A large data study [32][33] showed that admission hemoglobin levels are closely associated with mortality after septic infection, with a 7% increase in the 28-day risk of death for every 1-unit increase in HGB when HGB is in the range of 12.8-20.7 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers such as ferritin, hemoglobin, and lactate dehydrogenase (LDH) have been investigated in numerous clinical settings, including sepsis in children and adults [15][16][17][18][19][20][21]. Moreover, leukocytes, lymphocytes, and the biomarkers CK, CRP, LDH, AST, ferritin, and IL-6 accurately determine the inflammatory condition of newborns in some infections [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin reflects oxygen-carrying capacity and erythropoiesis. Hemoglobin plays a crucial role in both the immune response to infections and the physiological processes of leukocytes [20].…”
Section: Introductionmentioning
confidence: 99%